2020
DOI: 10.3389/fnins.2019.01446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rocking Movements on Afternoon Sleep

Abstract: Study Objectives: Gentle rocking movements provided by a moving bed have been proposed as a promising non-pharmacological way to promote sleep. In rodents the sleep promoting effect of rocking movements depended on the peak acceleration (named "stimulation intensity") perceived by the vestibular system. We set out to verify previous reports on the sleep promoting effect of rocking movements and to investigate the importance of stimulation intensity in this process. Methods: Side-to-side rocking movements along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 37 publications
4
31
2
Order By: Relevance
“…Vestibular stimulation using subjectively preferred stimulation direction and intensity did not improve sleep in our sample of elderly participants. Unlike studies in younger adults, we did not observe a facilitation of sleep onset, more deep sleep or an increase in the number or density of sleep spindles (Omlin et al, 2018;Shibagaki et al, 2017;Woodward et al, 1990). On the contrary, we observed reduced delta power, suggesting a reduced sleep depth under the influence of rocking movements.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Vestibular stimulation using subjectively preferred stimulation direction and intensity did not improve sleep in our sample of elderly participants. Unlike studies in younger adults, we did not observe a facilitation of sleep onset, more deep sleep or an increase in the number or density of sleep spindles (Omlin et al, 2018;Shibagaki et al, 2017;Woodward et al, 1990). On the contrary, we observed reduced delta power, suggesting a reduced sleep depth under the influence of rocking movements.…”
Section: Discussioncontrasting
confidence: 99%
“…When a rotational component is added to the stimulation, it is clear to the body that the stimulation is tilt and, thus, the sensory mismatch is solved. This could explain the difference between our findings and previous reports of a promotion of sleep through rocking movements (Bayer et al, 2011;Perrault et al, 2019;Shibagaki et al, 2017). Twelve out of 18 subjects in the study by Omlin and colleagues selected movements with a rotational component, and this could explain why also in this study only a weak effect of vestibular stimulation on sleep was observed (Omlin et al, 2018).…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations